2016
DOI: 10.1055/s-0042-116145
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of epidermal cell sheets by endoscopic balloon dilatation to avoid esophageal re-strictures: initial experience in a porcine model

Abstract: Background and study aims: Epidermal cell sheet (ECS) transplantation immediately after aggressive endoscopic submucosal dissection (ESD) has been shown to be safe and effective in the prevention of esophageal strictures. This study evaluated the feasibility of ECS transplantation after endoscopic balloon dilation (EBD) in a porcine model. Methods: Six pigs underwent circumferential esophageal ESD under general anesthesia. Two weeks later, two pigs underwent EBD and transplantation of an autologous ECS, two un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…First, the ESD ulcer might be too large to demonstrate the effect of cell sheet transplantation. We performed a large, 4-5 cm long circumferential ESD, but the artificial ulceration was shorter and more hemi-circumferential than those in previous reports [19][20][21]. We attached six to eight-cell sheets per ESD ulcer, and this number was insufficient to prevent long stricture.…”
Section: Discussionmentioning
confidence: 98%
“…First, the ESD ulcer might be too large to demonstrate the effect of cell sheet transplantation. We performed a large, 4-5 cm long circumferential ESD, but the artificial ulceration was shorter and more hemi-circumferential than those in previous reports [19][20][21]. We attached six to eight-cell sheets per ESD ulcer, and this number was insufficient to prevent long stricture.…”
Section: Discussionmentioning
confidence: 98%
“…In an animal model, Kobayashi et al. [ 92 ] reported that even intractable anastomotic stricture occurs at the stage of repair of mucosal laceration after EBD. In this study, transplanting epidermal cell sheets to the laceration site after EBD could reduce the extent of stricture.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The incidence of stricture was 10%. They have also succeeded in developing a logistics system and new devices to collect materials from clinics, transport them to the remote cell proceeding center, and return the cultured AOMECs for endoscopic transplantation [ 96 , 97 , 98 , 99 ].…”
Section: Regenerative Medicinementioning
confidence: 99%